Effectiveness of Tai Chi exercise on balance, falls, and motor function in older adults: a meta-analysis - Li, Liangxing; Guo, Shoujun; Ding, Bing; Zhang, Jinsong (Frontiers in Medicine, 2024)
Objective:This study systematically evaluated Tai Chi's effects on balance, fall prevention, and physical function in older adults.:A comprehensive literature search of PubMed, Web of Science, and EMbase databases included randomized controlled trials published up to August 2024. The meta-analysis used RevMan 5.4 and applied the GRADE framework to assess evidence quality. Results:Twenty-two studies met the criteria. Tai Chi significantly improved balance and physical function, particularly in the Berg Balance Scale(BBS), one-leg standing with eyes closed(OLS-C), and timed up-and-go test (TUG). Fear of falling (FOF)also reduced, though changes in Tinetti Balance Test(TBT) and Short Physical Performance Battery(SPPB) were not statistically significant.Chi effectively enhances balance and physical function in older adults, with notable potential for fall risk reduction. While some tests showed no significant effect, overall results support Tai Chi as a valuable intervention to promote older adults' health.